2021
DOI: 10.17993/3cemp.2021.100347.137-169
|View full text |Cite
|
Sign up to set email alerts
|

Women entrepreneurial leaders as harbingers of economic growth: evidences from an emerging market of South Asia

Abstract: Global economy is driven by entrepreneurs operating micro, small, medium, and large-scale enterprises (M-SMLEs). This probe integrates three distinct domains, entrepreneurship, leadership, and gender, particularly women. In a previous study, one of the co-authors investigated such phenomenon that comprised motivations and pre-and-post venture challenges for women entrepreneurial leaders and devised a conceptual framework. This inquiry applies quantitative methods to empirically test and validate such framework… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 56 publications
0
6
0
Order By: Relevance
“…Using Amos software, structured equation modelling (SEM) was availed to test the hypotheses. Through data normality test, it was learnt that Skewness and Kurtosis stood in the prescribed ranges of ±1.5, which confirmed normality of constructs (Byrne, 2013;Hair et al, 2015). In factor loadings, few items with loading up to .5 and insignificant T values below 1.96 values were excluded, and items with loading of .7 and significant T values up to or greater than 1.96 were taken for further testing.…”
Section: Discussionmentioning
confidence: 67%
See 2 more Smart Citations
“…Using Amos software, structured equation modelling (SEM) was availed to test the hypotheses. Through data normality test, it was learnt that Skewness and Kurtosis stood in the prescribed ranges of ±1.5, which confirmed normality of constructs (Byrne, 2013;Hair et al, 2015). In factor loadings, few items with loading up to .5 and insignificant T values below 1.96 values were excluded, and items with loading of .7 and significant T values up to or greater than 1.96 were taken for further testing.…”
Section: Discussionmentioning
confidence: 67%
“…A study in Malaysia emphasized the significance of religious values such as honesty and need to fulfill obligations (Makhbul & Hasun, 2011). Zulkifli and Rosli (2013) asserted that religiosity has a moderating role in the entrepreneurial success. It can be concluded that there is not a single factor but rather, a combination of factors that contribute to the success of entrepreneurial venture (Thien, 2016).…”
Section: Entrepreneurial Successmentioning
confidence: 99%
See 1 more Smart Citation
“…Several scholars concurred that more research is necessary to fully understand the circumstances of effective female entrepreneurial leadership in various situations and environments (Dean & Ford, 2017;Dunn et al, 2014;Harrison et al, 2015;Matsa & Miller, 2014). Scholars emphasized the research gap to further discover entrepreneurial leadership regarding women leaders (Dean & Ford, 2017;Kimbu et al, 2021;Santos & Neumeyer, 2021, Qureshi et al, 2021.…”
Section: The Studymentioning
confidence: 99%
“…In addition, researchers identified recent changes in female entrepreneurship and its relationship to leadership (Dean & Ford, 2017). Women have been actively engaged in practically every field and industry, and their involvement in politics and business appears to be increasing (Hoyt & Murphy, 2016;Qureshi et al, 2021).…”
mentioning
confidence: 99%